Konsep Strategi Pemasaran Jasa Pendidikan - Mahmud Mahmud (Prodi PAI Fakultas Tarbiyah IAI Uluwiyah Mojokerto, 2021)
Education is a non-profit institution or institution engaged in education services. In addition, competition between educational institutions is getting tighter. Thus, in this case educational providers are required to always be creative to explore the distingsi and excellence of the institution to be needed and demanded by the education customer. The marketing of educational services is not a business activity for the managed schools to have students, but it is the responsibility of education providers to the wider community about the education services that have been, are, and will do. Characteristics of education services, namely: a) Intangibility, b) Perishability, c) Inseparability, d) Less standardized and uniform. In educational marketing, it is necessary to have an education marketing mix. The marketing mix in the educational context are very important elements and can be integrated in such a way as to produce a marketing strategy that can be used to win the competition. The marketing mix consists of 7P ie product, price, place, promotion, people, physical evidence, process. The strategic measures of education services marketing are: Market identification, market segmentation and positioning, product differentiation, madrasah / school service, and marketing communications. Five Pillars of education services: a) make it easy, b) make it relevant, c) make it fresh, d) manage it, e) measure it.